Adjustment and Characterization of an Original Model of Chronic Ischemic Heart Failure in Pig - Laurent Barandon; Joachim Calderon; Patricia Réant; Dominique Caillaud; Stéphane Lafitte; Xavier Roques; Thierry Couffinhal; Pierre Dos Santos (Cardiology Research and Practice)
We present and characterize an original experimental model to create a chronic ischemic heart failure in pig. Two ameroid constrictors were placed around the LAD and the circumflex artery. Two months after surgery, pigs presented a poor LV function associated with a severe mitral valve insufficiency. Echocardiography analysis showed substantial anomalies in radial and circumferential deformations, both on the anterior and lateral surface of the heart. These anomalies in function were coupled with anomalies of perfusion observed in echocardiography after injection of contrast medium. No demonstration of myocardial infarction was observed with histological analysis. Our findings suggest that we were able to create and to stabilize a chronic ischemic heart failure model in the pig. This model represents a useful tool for the development of new medical or surgical treatment in this field.